Creating BHb-imprinted magnetic nanoparticles with multiple binding sites. Issue 2 (7th December 2016) - Li, Yanxia; Chen, Yiting; Huang, Lu; Lou, BenYong; Chen, Guonan
Abstract : A kind of protein imprinted over magnetic Fe3 O4 @Au multifunctional nanoparticles (NPs) with multiple binding sites was synthesized and investigated. Abstract : A kind of protein imprinted over magnetic Fe3 O4 @Au multifunctional nanoparticles (NPs) with multiple binding sites was synthesized and investigated. Magnetic Fe3 O4 @Au NPs as carrier materials were modified with 4-mercaptophenylboronic acid (MPBA) and mercaptopropionic acid (MPA) to introduce boronic acids and carboxyl groups. Using Bovine Hemoglobin (BHb) as a template, a polydopamine(PDA)-based molecular imprinted film was fabricated to produce a kind of magnetic molecularly imprinted nanoparticle (MMIP), possessing multiple binding sites with benzene-diol, amino groups, boronic acids and carboxyl groups. The MMIPs exhibited an excellent imprinting effect and adsorption capacity (89.65± 0.38 mg g −1 ) toward the template protein. The results show that the MMIPs reached saturated adsorption at 0.5 mg mL −1 within 90 min. The synthesized MMIPs are suitable for the removal and enrichment of the template protein in proteomics. The strategy of multiple binding sites paves the way for the preparation of functional nanomaterials in molecular imprinting techniques.